(untitled) (London, 2007)
The book combines informative narrative and gorgeous photography to bring over 130 global destinations to life. It is the ultimate holiday planner highlighting the world's most spectacular places anf the best time to visit them
Keywords: Travel,Du hành; Sách hướng dẫn